Two new species of the gorgonian inhabiting barnacle, Conopea (Crustacea, Cirripedia, Thoracica), from the Gulf of Guinea - Dana Carrison-Stone; Robert Van Syoc; Gary Williams; Brian Simison (ZooKeys, 2013)
Two new species of Conopea (Say 1822) are described from the Gulf of Guinea: Conopea saotomensis sp. n. and Conopea fidelis sp. n. These two new species were collected from the historically isolated volcanic islands of São Tomé and Príncipe. The relationship between Conopea saotomensis sp. n., Conopea fidelis sp. n. and two other Atlantic barnacle species, Conopea calceola (Ellis 1758) and Conopea galeata (Linnaeus 1771), is examined. The methods employed are the construction of a molecular phylogeny using mitochondrial COI and nuclear H3 gene sequence data along with morphological comparisons of calcareous and cuticular body parts. It is found that Conopea saotomensis sp. n., Conopea fidelis sp. n. and Conopea calceola are most closely related to each other but the relationship among them is unresolved. Gorgonian hosts are identified. Preliminary observations show species level host specificity for C. fidelis sp. n.